The Saminist Movement of the Kendeng Mountains Complex of Java during the Dutch Colonial and Indonesiaâs Reform Eras - Nawiyanto, Nawiyanto; Endrayadi, Eko Crys (TAWARIKH, 2017)
ABSTRACT: Saminist community is widely known for its strong resistance tradition. One major similar feature of the Saminist resistance movement during the Colonial and Reform periods is the rejection to the external influences and their related agencies that have been regarded as threatening the Saminist livelihoods and values. This article discusses the Saminist resistance movement in the Dutch colonial period and the era of Reform, thus displaying a historical comparison of a local community in a different period. By using the historical method and drawing upon various available sources that have been reached, this article aims to explain the similarities and/or differences in the Saminist resistance movement in the past and the present, in terms of the conditional factors giving birth to the movement and characteristics of the Saminist movement. It is argued that the Saminist resistance movement has changed from a socio-economy-based resistance movement in the context of colonial exploitation to an environment-based resistance movement. This change at once also trasformed it from an old social movement into a new social movement. In addition to raising the new issue that is radically different, the novelty of the Saminist resistance movement in the Reform period is also evident in the form of the appearance of Saminist women actively in the forefront of resistance actions that they did, and the alliances it built with other groups having concerns with the environmental issues.KEY WORDS: Resistance Movement; Saminist Community; Kendeng Mountains Complex; Dutch Colonial Period; Reform Period.Â  About the Authors: Prof. Dr. Nawiyanto and Dr. Eko Crys Endrayadi are the Lecturers at the Department of History, Faculty of Letters UNEJ (University of Jember), Jalan Kalimantan No.37, Jember 68121, East Java, Indonesia. For academic interests, the authors are able to be contacted via their e-mails address at: nawiyanto.sastra@unej.ac.id and ekocrys@yahoo.co.idHow to cite this article? Nawiyanto & Eko Crys Endrayadi. (2017). âThe Saminist Movement of the Kendeng Mountains Complex of Java during the Dutch Colonial and Indonesiaâs Reform Erasâ in TAWARIKH: International Journal for Historical Studies, Vol.8(2) April, pp.117-130. Bandung, Indonesia: Minda Masagi Press and UIN SGD Bandung, ISSN 2085-0980. Chronicle of the article: Accepted (September 23, 2016); Revised (January 20, 2017); and Published (April 28, 2017).